2021
DOI: 10.1007/s00484-021-02202-0
|View full text |Cite
|
Sign up to set email alerts
|

Heat strain and mortality effects of prolonged central European heat wave—an example of June 2019 in Poland

Abstract: The occurrence of long-lasting severe heat stress, such as in July–August 2003, July 2010, or in April–May 2018 has been one of the biggest meteorological threats in Europe in recent years. The paper focuses on the biometeorological and mortality effects of the hot June that was observed in Central Europe in 2019. The basis of the study was hourly and daily Universal Thermal Climate Index (UTCI) values at meteorological stations in Poland for June 2019. The average monthly air temperature and UTCI values from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…The occurrence of such thermally anomalous months may pose a direct threat to human health and lives, cause hindrance to transport and reduce the performance of the economy (Blazejczyk and Twardosz, 2010). The most extreme events in Europe's climate to date have included the extremely cold February1929 (Gumiński, 1931) and 1956 (Dizerens et al ., 2017), the January 1963 (Hirschi and Sinha, 2007), and the unusually warm August 2003 (Chase et al ., 2006), 2010 (Sidorenkov and Sumerova, 2012), as well as the June 2019 (Blazejczyk et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of such thermally anomalous months may pose a direct threat to human health and lives, cause hindrance to transport and reduce the performance of the economy (Blazejczyk and Twardosz, 2010). The most extreme events in Europe's climate to date have included the extremely cold February1929 (Gumiński, 1931) and 1956 (Dizerens et al ., 2017), the January 1963 (Hirschi and Sinha, 2007), and the unusually warm August 2003 (Chase et al ., 2006), 2010 (Sidorenkov and Sumerova, 2012), as well as the June 2019 (Blazejczyk et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The daily maximum UTCI was selected to reflect heat stress since human beings were hypothesized to be vulnerable to extreme weather conditions. According to the thresholds of the UTCI (Błażejczyk et al, 2010 ), thermoneutral conditions referred to UTCI between 9.1 and 26.0 °C, moderate heat stress referred to UTCI between 26.1 and 32.0 °C, strong heat stress referred to UTCI between 32.1 and 38.0 °C, and very strong heat stress referred to UTCI between 38.1 and 46.0 °C. In Hong Kong, none of the days in the analysis set was having extreme heat stress (UTCI ≥ 46.1 °C).…”
Section: Methodsmentioning
confidence: 99%
“…The UTCI not only incorporates multiple meteorological variables in a non-linear way, but, more importantly, it also classifies thermal stress based on human physiological responses. Ten thermal stress classifications, ranging from extreme cold stress (UTCI ≤ − 40.0 °C), to thermoneutral conditions (UTCI between 9.1 and 26.0 °C), and extreme heat stress (UTCI > 46.0 °C), were proposed to describe the extreme weather stress experienced by humans (Błażejczyk et al, 2010 ). However, investigations regarding the association between thermal stress and health outcomes, particularly heat stress, have been mostly conducted in Europe, which generally has a temperate climate.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Schwartz et al have revealed that with each 1 • C temperature decrease the mortality ratio rises by 0.49% and the frequency of all-cause, circulatory, coronary heart disease, and ST-segment elevation myocardial infarction (STEMI) death (4). Blazejczyk et al (5) have shown that the number of deaths attributed to a strong heat stress was five times higher and the total mortality was almost 10% higher in June 2019 than the average for the period of 2010-2018 in Poland. Also, the exposure to an acute air pressure decrease more than 10.7 hPa within 7 days before STEMI increased the rate of STEMI (odds ratio 1.12, 95% CI 1.03-1.21) (6).…”
Section: Introductionmentioning
confidence: 98%